Knowledge, Attitude and Practice Regarding Hormonal Emergency Contraception Aamong Married Female Staff in Universiti Putra Malaysia - Sharj Abad, Fatemeh Najafi (2010)
Emergency Contraception (EC) is a back-up method of contraceptive emergencies, which women can use within the first few days after unprotected intercourse to prevent an unwanted pregnancy. In Malaysia, the use of modern contraceptive method is low whereby only 30% of married women (15-49) used it. Studies have shown unwanted pregnancies among young women are increasing. The aim of this study was to determine the factors and its relationship on knowledge, attitude and practice of hormonal EC among married female staff in Universiti Putra Malaysia (UPM). A cross- sectional study was conducted among married female staffs using stratified random sampling from 15 faculties in UPM. Data on sociodemographic, reproductive health factors, knowledge, attitude and practice of EC were gathered using self-administered questionnaire. The response rate was 87.24%. Respondents comprised of 81(27.6%) academic and 213(78.4%) non academic staff. The mean age of respondent was 35.8 ± 9 years old. Mistimed pregnancy and unwanted pregnancy were reported by 35% and 13.6% of respondents respectively. 45.1% of women practiced contraception. The mean knowledge score on EC was 5.89 ± 4.17 and the mean attitude score was 28.24 ± 6.53. There was significant difference in the mean knowledge score of academic and non academic staff [t (292) =3.168; p=0.002]. A low and positive relationship was found between knowledge and attitude (r=0.269; p= 0.0001]. Respondents who used EC had more positive attitude compared to non users [t (292) = -7.188; p=0.0001]. Overall, only 11.2% of women had ever used EC. Logistic regression for predictor variables showed positive attitude (p= 0.027) and counseling with doctors (p=0.037) were significant. This study showed knowledge of hormonal EC was low among married female staff particularly among non academic staff in UPM. The used of contraceptive methods was also low and only small proportion of women had ever used EC pill. Large proportion of non contraceptive users can lead to high risk unintended pregnancy. Hence there is a need to provide accurate information and counseling on effective use of EC.